2021
DOI: 10.1111/dar.13370
|View full text |Cite
|
Sign up to set email alerts
|

A new quantitative drug checking technology for harm reduction: Pilot study in Vancouver, Canada using paper spray mass spectrometry

Abstract: Introduction. Drug checking services for harm reduction and overdose prevention have been implemented in many jurisdictions as a public health intervention in response to the opioid overdose crisis. This study demonstrates the first on-site use of paper spray mass spectrometry for quantitative drug checking to address the limitations of current on-site drug testing technologies. Methods. Paper spray mass spectrometry was used to provide on-site drug checking services at a supervised consumption site in the Dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 36 publications
(43 reference statements)
0
40
0
Order By: Relevance
“…Publication bias may limit the representativeness of the included literature, as studies not showing positive impacts of DCS could be under‐represented. Timing of the search is another limitation, and several peer‐reviewed articles have been published since [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ], including one Canadian study among drug sellers [ 100 ]. Our eligibility criteria excluded studies where DCS were not implemented although they may have reported outcomes on our domains, such as facilitators and barriers to use of DCS [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication bias may limit the representativeness of the included literature, as studies not showing positive impacts of DCS could be under‐represented. Timing of the search is another limitation, and several peer‐reviewed articles have been published since [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ], including one Canadian study among drug sellers [ 100 ]. Our eligibility criteria excluded studies where DCS were not implemented although they may have reported outcomes on our domains, such as facilitators and barriers to use of DCS [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Publication bias may limit the representativeness of the included literature, as studies not showing positive impacts of DCS could be under-represented. Timing of the search is another limitation, and several peer-reviewed articles have been published since [99][100][101][102][103][104][105][106][107][108][109][110][111], including one Canadian study among drug sellers [100].…”
Section: Study Qualitymentioning
confidence: 99%
“…Lacking tolerance for opioids, users of (expected) nonopioid street drugs can experience overdoses and fatalities when even a very small amount of a potent opioid such as fentanyl or analog is present in their drug. Recent publications in the scienti c literature and popular press indicate adulteration of non-opioids with fentanyl is occurring with more frequency, often having fatal consequences [1,48,49,50] As drug testing methods evolve, however, more sensitive and comprehensive testing methods such as portable gas chromatograph-mass spectrometry and Fourier-transform infrared spectroscopy (FTIR) that can be provided as point-of-care testing are being evaluated and could soon come into wider use[16, 30,51,52]. These testing methods represent what we assess as a reasonable compromise between more advanced but expensive and technologically complex testing methods and accessible, easy-to-use but less informative methods available for take-home use.…”
Section: Discussionmentioning
confidence: 99%
“…10 The PS-MS analysis of illicit drugs has been reported in the literature. [11][12][13][14] Unfortunately, detection limits for direct THC or THC-COOH analysis with PS-MS tend to be high due to the poor ionization efficiency of cannabinoids. Some groups have increased sensitivity for cannabinoids with PS-MS, but at the cost of including undesirable reagents and/or additional sample preparation steps.…”
Section: Introductionmentioning
confidence: 99%